The Ventral Midline Thalamus Mediates Hippocampal Spatial Information Processes upon Spatial Cue Changes - Jung, Dahee (J Neurosci, 2019)
The ventral midline thalamus, consisting of the reuniens and rhomboid nuclei (RE/Rh), is a thalamic structure interconnected with the limbic systems including the hippocampus. Recently, many studies have revealed that this structure plays distinctive roles in spatial learning and memory in collaboration with hippocampal functions. However, what aspects of spatial information process are influenced by the RE/Rh is not clearly known. To elucidate the roles of RE/Rh in spatial information processing and its effects on hippocampal activity, specifically with the manipulation of spatial contents, we measured hippocampal-dependent spatial memory performance and hippocampal place cell activities after RE/Rh lesion using male C57BL/6J × 129/SvJae hybrid mice. We found that the lesion altered the behavioral aptitude in recognizing locational changes of an object. Furthermore, CA1 place cells in the lesion group showed different spatial representation patterns in recognizing the environment with cue locational changes compared with the control group. Interestingly, the patterns of CA1 place cells in recognizing the same environment previously visited were not disrupted in the lesion group compared with the control group. These findings demonstrate that the ventral midline thalamus (RE/Rh) is important in recognizing the spatial relationships, especially when spatial rearrangement of cue position was introduced. SIGNIFICANCE STATEMENT The ventral midline thalamic nuclei (reuniens and rhomboid) interact with the hippocampus to influence various cognitive functions requiring spatial memories, yet what aspects of spatial information process are influenced by these nuclei is not clearly known. Here, we reveal that these nuclei play a crucial role in modulating hippocampal properties only with locational rearrangement of cues, not with the familiar arrangement. These nuclei are distinctively involved in cue-dependent spatial information processes of CA1 place cells. In particular, we suggest that these nuclei modulate spatial information processing on discrete components, especially when the spatial cue relationship is modified.